Media in Serbia: Creativity or Quasi Creativity? - Slađana Stamenković (In Medias Res, 2016)
Information technologies, with their explosive growth and stunning effects, provided the definitive seal the emergence of a new era of knowledge. They created an infrastructure for rapid exchange of information and facilitate the accelerated globalization of world markets, new organizational forms and methods of communication and work. Progress in information and telecommunication technologies has enabled the processing, storing, receiving and sending information in almost any possible shape, regardless of distance, time, volume and with less cost. In today strongly interconnected world, resources such as creativity and innovation have become the most important in relation to all the others. The new rules apply, globally, and at the micro and macro level. The problem of the lack of ethics and fall of competence, reputation and the confidence of the public in the media, is the perennial problem of Serbian media space. The general tabloidization society, the decline in the quality of the media supply, with an increase in the number of tabloid media, along with the simultaneous appearance of that tabloid elements acquire even the media who had been in force for relevant, high-quality and serious feature is the most important characteristics the media-sphere in Serbia. Rating and circulation are the most important and creativity is usually put into operation profits media owners, holders of political and/or economic power. Creative efforts can be seen in radio and television public service but they, like most cultural events, are of secondary importance (for other programs). While in Serbia, still, as in the region can not live fully in the information age, the importance of creative cultural, media flows of design knowledge, information and creativity is cause for reflection on this topic, in order to explain and understand the changes which we are witnesses and those to come.